Pattern Specificity of Contrast Adaptation. (February 2014) - Anstis, Stuart
Contrast adaptation is specific to precisely localised edges, so that adapting to a flickering photograph makes one less sensitive to that same photograph, but not to similar photographs. When two low-contrast photos, A and B, are transparently superimposed, then adapting to a flickering high-contrast B leaves no net afterimage, but it makes B disappear from the A+B picture, which now simply looks like A.